2022
DOI: 10.1038/s41420-022-01158-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of respiratory V-ATPase and calprotectin in SARS-CoV-2 infection

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) represents a pandemic threat that has been declared a public health emergency of international concern, whereas the effects of cellular microenvironment in the pathogenesis of SARS-CoV-2 are poorly understood. The detailed message of intracellular/lysosome pH was rarely concerned in SARS-CoV-2 infection, which was crucial for the cleavage of SARS-CoV-2 spike (S) protein. Calprotectin, an endogenous danger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…ATP6V1 was upregulated in patients with antibody generation. This protein acidifies cellular compartments as well as the extracellular environment, which was previously found upregulated in SARS-CoV-2-infected cells [ 39 ]. Interestingly, it has been reported that an acidic pH environment facilitates SARS-CoV-2 infection [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…ATP6V1 was upregulated in patients with antibody generation. This protein acidifies cellular compartments as well as the extracellular environment, which was previously found upregulated in SARS-CoV-2-infected cells [ 39 ]. Interestingly, it has been reported that an acidic pH environment facilitates SARS-CoV-2 infection [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…ATP6V0D1 was observed to be upregulated in A549 cells transfected with SARS-CoV-2 S plasmid and intracellular/lysosomal pH was observed to be decreased. 50 TCTN2, another regulated protein is shown to be associated with osteoarthritis. 51 PHLDA3 knock down is observed to be negatively affecting colony forming efficiency of MM468 cells expressing myr-Akt and high frequency of chromosome loss at PHLDA3 locus is also reported in large cell neuroendocrine carcinoma (LCNEC).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…SARS-CoV-2 were shown to be increasing the expression of V-ATPase. 50 Pathway involving other hub genes TGFB1, TGFBR2, and LGALS3 was dendritic cell differentiation. Further analysis of pathways involving heart hub genes RAB7A, ATPV0D1, and LAMP2 were associated with phagosome related processes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This observation is in line with a previous report which showed high expression of SERINC2 gene in COVID-19 patients [67] (Table 5). The ATP6V0C (ATPase H+ Transporting V0 Subunit C) is a component of V-ATPase (vacuolar ATPase) which inhibits lysosomal acidification mechanism by blocking the passage of H + via lysosomal membrane [68] and it has been found that S protein of SARS-CoV-2 induces the higher expression of V-ATPase within COVID-19 patients [69].…”
Section: Discussionmentioning
confidence: 99%